The effectiveness and safety of regional citrate anticoagulation in intermittent haemodialysis/haemodiafiltration -- a systematic review. - Aijun Fang; Wiechula, Richard (Renal Society of Australasia Journal, 2018)
Background: Haemodialysis requires anticoagulation to prevent thrombosis in the extracorporeal circuit (ECC), usually with heparin. However, systemic heparin anticoagulation is contraindicated when patients have active haemorrhage or bleeding risk or heparin-induced thrombocytopaenia type II. Regional citrate anticoagulation (RCA) has been suggested by many studies as an effective and safe alternative anticoagulation in these situations. However, to the authors' best knowledge, there are no systematic reviews exploring the efficacy and safety of RCA in intermittent haemodialysis/haemodiafiltration (IHD/IHDF). Aim: The review intends to explore the effectiveness and safety of RCA in IHD/IHDF. Methods: A comprehensive literature search was conducted and 14 studies were included. Two reviewers critically appraised the articles and then extracted data. Narrative synthesis was conducted on the extracted data due to the outstanding heterogeneity among the included studies. Results: Conventional RCA with calcium-free dialysate was an effective alternative anticoagulation method in IHD. Mild metabolic derangement, especially asymptomatic hypocalcaemia, was common and severe metabolic complications were mainly caused by operational errors. However, RCA with calcium containing dialysate compromised anticoagulation in the ECC. Conclusions: Conventional RCA with calcium-free dialysate is an efficacious and relatively safe alternative anticoagulation method in IHD. Point of care monitoring of calcium is necessary to ensure efficacy and safety.